Pemodelan dan Analisa Produktivitas Proses Pembekuan Produk Fillet Ikan Menggunakan Objective Matrix (OMAX) (Studi Kasus PT. Mandala Mulya Sakti Surabaya) - Kurniawan, Christian; Tjahyono, Rudy; Izzhati, Dwi Nurul (Universitas Dian Nuswantoro, 2017)
Way in increasing the value of productivity in manufacturing and service companies are usually always faced with many constraints factors such as human, machine, material, information or energy. PT. Mandala Mulya Sakti Surabaya is one example of a fish processing manufacturing company experiencing problems related to productivity decline. The decrease of productivity occurred in July 2016 where the freezing unit of dori fish fillet with significant value so that handling effort is needed. This research uses Objective Matrix (OMAX) as an effort to evaluate the value of productivity by modeling and analyzing the productivity of freezing process of dori fish product, then the result of scientific analysis will be used as benchmark of productivity improvement in the future. Technical rather than the use of OMAX is to determine the criteria ratios, search data using questionnaires and utilize AHP methods to determine the weight, followed by the calculation of ratios and the determination of the value boundary, then the final stage is the creation of OMAX table to calculate the value of productivity. The results of this study indicate that the lowest productivity value occurred in July of 2016 of 5.08 and the highest in April 2017 amounted to 468.12. These results can be a reference in future productivity improvements